(untitled) (Nigerian Journal of Technology, 2019)
This research was carried out to investigate the effects of cooling on Photovoltaic (PV) module performance in a tropical region. A Photovoltaic module system was set up in an outdoor environment to expose it to real life operating conditions at the Quadrangle, Faculty of Technology, University of Ibadan, Oyo State, Nigeria (7°24´7.0632´´N, 3° 55´ 2.3268´´E), where all the measuring devices were connected to extract all data that determine the power generated by the PV. The experiment was repeated under water cooling condition. Time series analysis was performed on the data collected from the experimental set up. The results indicated that under water cooling condition, the temperature decreased maximally by . This leads to a percentage increase of of the open circuit voltage, the maximum power delivered by the PV module also increases by and this effectively increases the conversion efficiency of the PV module by . The cooling arrangement maintains the temperature to a certain limit, between and thereby avoiding long term thermal degradation. The result of this work further corroborated the results of works done from the temperate region. http://dx.doi.org/10.4314/njt.v38i3.23